Single-Item Chronotyping (SIC), a method to self-assess diurnal types by using 6 simple charts. (1st January 2021) - Putilov, Arcady A.; Sveshnikov, Dmitry S.; Puchkova, Alexandra N.; Dorokhov, Vladimir B.; Bakaeva, Zarina B.; Yakunina, Elena B.; Starshinov, Yuri P.; Torshin, Vladimir I.; Alipov, Nikolay N.; Sergeeva, Olga V.; Trutneva, Elena A.; Lapkin, Michael M.; et al.
Abstract: Research on individual differences in the fields of chronobiology and chronopsychology mostly focuses on two – morning and evening – chronotypes. However, recent developments in these fields pointed at a possibility to extend chronotypology beyond just two chronotypes. We examined this possibility by implementing the Single-Item Chronotyping (SIC) as a method for self-identification of chronotype among six simple chart options illustrating the daily change in alertness level. Of 2283 survey participants, 2176 (95%) chose one of these options. Only 13% vs. 24% chose morning vs. evening type (a fall vs. a rise of alertness from morning to evening), while the majority of participants chose four other types (with a peak vs. a dip of alertness in the afternoon and with permanently high vs. low alertness levels throughout the day, 15% vs. 18% and 9% vs. 16%, respectively). The same 6 patterns of diurnal variation in sleepiness were yielded by principal component analysis of sleepiness curves. Six chronotypes were also validated against the assessments of sleep timing, excessive daytime sleepiness, and abilities to wake or sleep on demand at different times of the day. We concluded that the study results supported the feasibility of classification with the 6 options provided by the SIC. Highlights: The Single-Item Chronotyping (SIC) was proposed for self-identifying 6 chronotypes. Of 2283 survey participants, 2176 (95%) chose one of these 6 chronotypes. Four other than morning and evening chronotypes were the majority in this sample. The SIC was validated against various multi-item chronopsychological self-assessments.